Effects of tissue flossing and dynamic stretching on hamstring stiffness and flexibility in light volleyball enthusiasts: a randomized controlled trial - Ren, Kang; Zhao, Zhendong; Wu, Lu; Luo, Liyu (Frontiers in Physiology, 2025)
IntroductionThis randomized controlled trial aimed to compare the acute and sustained effects of tissue flossing (TF) versus dynamic stretching (DS) on hamstring muscle stiffness and flexibility in light volleyball (LVB) enthusiasts.MethodsThirty-seven participants were randomly assigned to TF, DS, or placebo groups. Muscle stiffness was evaluated using shear-wave elastography, measuring Young’s modulus at the distal and proximal regions of the biceps femoris long head and semitendinosus. Flexibility was assessed via passive knee extension (KE), straight leg raise (SLR), and forward flexion distance (FFD) at baseline, immediately post-intervention, and 30 min post-intervention.ResultsThe results demonstrated that TF significantly reduced muscle stiffness compared to DS at the 30-min mark, particularly in the semitendinosus [distal: mean difference = −43.40 kPa, 95% CI (–80.65, −6.16), p = 0.007; proximal: −51.13 kPa, (–101.20, −1.05), p = 0.040]. However, no significant differences were observed between the TF and DS groups in flexibility outcomes (KE, SLR, or FFD) at any time point.DiscussionThese findings indicate that while TF offers a prolonged reduction in hamstring stiffness—suggesting potential benefits in injury prevention and prolonged performance—its effect on functional flexibility remains comparable to that of dynamic stretching. TF may serve as an effective warm-up intervention for athletes requiring sustained decreases in muscle stiffness during activities.